1984
DOI: 10.3109/03630268408996956
|View full text |Cite
|
Sign up to set email alerts
|

HB Wayne, the Frameshift Variant with Extended α Chains Observed in a Caucasian Family from Alabama

Abstract: The presence of the alpha-globin frameshift mutant, Hb Wayne, in three generations of a second family is described. The data include a hematological evaluation of the four heterozygotes, structural characterization of the variant, the use of HPLC for the separation of tryptic and chymotryptic peptides, functional analyses of the isolated variant showing high affinity for oxygen and the (near) absence of a Bohr effect, and alpha chain gene organization analyses with restriction endonuclease technology suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In the third exon, other unstable variants were described; specifically, four variants create a very long α-chain: α2 cod90-93 (−8bp) or HBA2: c.272_279delAGCTTCGG (stop at codon 170) [48], α2 cod116-119 (−11bp) (stop at codon 166) [52]; Hb Pak Num Po (stop at codon 175) [55]; Hb Wayne (stop at codon 147) [57]. Patients compound heterozygous for these variants and an α0-thal or α+ -thal mutation are characterized by more severe phenotypes, including transfusion dependence.…”
Section: Mrna Variant In Globin Mutantsmentioning
confidence: 99%
“…In the third exon, other unstable variants were described; specifically, four variants create a very long α-chain: α2 cod90-93 (−8bp) or HBA2: c.272_279delAGCTTCGG (stop at codon 170) [48], α2 cod116-119 (−11bp) (stop at codon 166) [52]; Hb Pak Num Po (stop at codon 175) [55]; Hb Wayne (stop at codon 147) [57]. Patients compound heterozygous for these variants and an α0-thal or α+ -thal mutation are characterized by more severe phenotypes, including transfusion dependence.…”
Section: Mrna Variant In Globin Mutantsmentioning
confidence: 99%
“…This hemoglobin variant has been reported previously and referred to as hemoglobin Wayne. [10][11][12] After revealing the presence of this hemoglobin variant, boronate affinity chromatography was used to measure A1c, which was found to be 4.7%. This value was more consistent with reported blood glucose levels and further supported the fact the patient indeed did not have diabetes.…”
Section: Case Reportmentioning
confidence: 99%
“…The presence of an extra peak made interpretation of HbA 1c difficult as it overlapped with the HbA 1c peak, resulting in an estimate of 15.2% for the concentration of HbA 1c . The extra peak overlapped so considerably with the HbA 1c peak that the composite peak only exhibited extremely subtle indication of its dual nature [23]. Identification of the haemoglobin variant was by electrospray mass spectrometry which demonstrated that 18.5% of the haemoglobin was variant and that the HbA 1c concentration was 6.1%.…”
Section: Clinical Casesmentioning
confidence: 99%
“…This was first described in 1976 in a Caucasian neonate in Pike County, Central Georgia, whose grandparents originated from Birmingham, Alabama, USA [24]. Two other families have been reported; one a Caucasian family from Michigan [23] and another from Canada [25].…”
Section: Clinical Casesmentioning
confidence: 99%